THE IMPROVEMENT OF SKILLS IN GIVING SIMPLE EXPLANATIONS AND IMPLEMENTING ACCEPTABLE CONCEPTS IN SALT HYDROLYSIS MATERIAL THROUGH GUIDED INQUIRY LEARNING MODEL. - ria septiana; ila rosilawati; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The aim of this research was to determine effectiveness of guided inquiry learning model in salt hydrolysis material in improving the skills in giving a simple explanation and implementing acceptable concept. Samples were 32 students in classroom XI science three as experiment and 31 students in classroom XI science four as control that have equal academic abilities. This was a quasi experiment research using non equivalent control group design.  Data analysis used a t-test of the n-Gain significant. The results showed that average value of n-Gain of skills in giving a simple explanation in experiment and control classrooms were 0.44 and 0.12 respectively; and average value of n-Gain for implementing acceptable concepts in experiment and control classrooms were 0.42 and 0.20 respectively with tcount (2.23) ttable (1.67). The conclusion is that the guided inquiry learning model in salt hydrolysis was effective in improving skills in giving simple explanations and implementing acceptable concepts by students.Keywords: guided inquiry, meteri salt hydrolysis ,giving a simple explanation and apply the concept of acceptable.